Characterization of the prescription of anxiolytics in institutionalized older adults in the Nursing Home (International Journal of Medical and Surgical Sciences, 2021)
The objective of this study was to characterize the prescription of anxiolytic medications used in the institutionalized elderly population at the Pinar del Río Nursing Home during 2017. A cross-sectional descriptive study was carried out, with retrospective data collection, on the prescription of anxiolytic medications in the population of institutionalized older adults in the Nursing Home, the form of use of the medications, their indication and prescription with elements of the therapeutic scheme was analyzed and factors that condition prescription habits. We worked with the universe (U = 98) of the study, which was made up of the total number of institutionalized patients who were consuming anxiolytics. Individual medical records were reviewed and a data collection model was created. The drug most consumed by older adults was nitrazepam (41.8%), this in turn being the most consumed by males, not so for females, which turned out to be chlorodiazepoxide (64.6%), the group The most prevalent age group was 60-69 years, likewise widowers and primary educational level, 79.5% of the elderly consume other drugs that have pharmacokinetic interaction. The professional who indicated the most was the family doctor, the prescription and intervals between doses were adequate, the prescription was considered non-rational. The prescription of anxiolytics in the population under study decreases as age increases, the most consumers are those of the male sex and those institutionalized due to family abandonment, this points to the need to continue working from the primary level of care since that is where these elders come from.
Keywords: prescription, anxiolytics, older adults, antidepressants, nursing homes, institutionalized.